2018
DOI: 10.1155/2018/6242173
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic of HPV Integration in the Genome and Transcriptome of Cervical Cancer Tissues

Abstract: High-risk HPV is clearly associated with cervical cancer. HPV integration has been confirmed to promote carcinogenesis in the previous studies. In our study, a total of 285 DNA breakpoints and 287 RNA breakpoints were collected. We analyzed the characteristic of HPV integration in the DNA and RNA samples. The results revealed that the patterns of HPV integration in RNA and DNA samples differ significantly. FHIT, KLF5, and LINC00392 were the hotspot genes integrated by HPV in the DNA samples. RAD51B, CASC8, CAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 23 publications
4
39
0
Order By: Relevance
“…For 40 specimens, the retrospective results of HPV type detection were given by commercial HPV type detection kits, which was approved by CFDA, and the detection method was FHGC. In the retrospective results, the HPV subtypes were mainly HPV16 and HPV18; the HPV multiple infection ratio was 35% (14/40), which was exactly consistent with the previous reports [17]. But Tau-protein kinase activity 2 2 2 3 6 Figure 6: GO categories assigned to all 6867 integration genes.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…For 40 specimens, the retrospective results of HPV type detection were given by commercial HPV type detection kits, which was approved by CFDA, and the detection method was FHGC. In the retrospective results, the HPV subtypes were mainly HPV16 and HPV18; the HPV multiple infection ratio was 35% (14/40), which was exactly consistent with the previous reports [17]. But Tau-protein kinase activity 2 2 2 3 6 Figure 6: GO categories assigned to all 6867 integration genes.…”
Section: Discussionsupporting
confidence: 88%
“…In their report, POU5F1B, FHIT, KLF12, HMGA2, KLF5, LRP1B, LEPREL1, DLG2, and SEMA3D were the hotspots. But the highfrequency integration sites reported by Li et al were FHIT, CASC8, KLF5, LINC00392, RAD51B, CASC21, ERBB2, TP63, TEX41, RAP2B, and MYC [17]. These highfrequency integration sites were quite different, which indicates that there were different high-frequency integration sites in different sample sources.…”
Section: Discussionmentioning
confidence: 88%
“…The integration of both HPV16 and HPV18 at the gene desert suggests that HPV coordinately affects oncogene alterations for cervical cancer formation [13,[64][65][66][67]. The integration hot spots in the gene desert include CASC8, CASC21, and POU5F1B [68,69]. Among 3667 breakpoints of HPV integration detected in cervical carcinoma (n = 104), cervical intraepithelial neoplasia (n = 26), and 5 cervical cancer cell lines, POU5F1B is the top site of integration (9.7%) [69].…”
Section: Association Of the 8q2421 Gene Desert With Oncogenesismentioning
confidence: 99%
“…There are very few studies on it at present. Li et al reported that CASC21 was a hotspot gene integrated by HPV in cervical cancer [31]. Interestingly, Zheng et al also found that CASC21 played an oncogenic role in CRC.…”
Section: Discussionmentioning
confidence: 99%